(untitled) (Research, Society and Development, 2022)
Introduction: Type 2 diabetes mellitus (DM2) is one of the most worrisome diseases worldwide due to its high prevalence, severe complications and individual damage to patients and the costs to health systems. With the increasing urbanization and world’s modernization, society’s concerns about maintaining healthy habits have been replaced whith another that grant a sedentary habits. Objective: To verify the impact of physical exercise (PE) on national and international scientific production in the period between 2017 and 2021. Methods: The study is characterized as an Integrative Literature Review. The PubMed database was verified, with a total of 150 articles for analysis and final selection. 134 articles that were not relevant were excluded. The sample consisted of 16 articles. Results and Discussion: Lifestyle has a great impact on the inflammatory state to which the body is subjected. The adoption of healthy behaviors, as simple as they may seem, are capable of bringing laboratory changes in patients with DM2. PE, as an important component of a healthy lifestyle (HLS), has the potential to provide changes in important health parameters. Conclusion: PE promotes changes at molecular and systemic levels, allowing the regulation of the secretion of pro-inflammatory molecules and peptides, whose action is therefore weakened, bringing the sedentary patient to serum levels close to physiological.